THE ROLE OF CRISES (FINANCIAL, MIGRANT AND COVID-19) IN THE RISE AND FALL OF THE RADICAL RIGHT POLITICAL PARTIES IN EUROPE - Krtolica, Marko (Ss. Cyril and Methodius University in Skopje - Iustinianus Primus Faculty of Law in Skopje - Iustinianus Primus Law Review, 2021)
The rise of the radical right political parties has marked the European political scene in the last two decades. The global financial crisis in 2007 and the migrant crisis in 2014, paved the way for the rise of the radical right parties in Europe. By raising their voice against political and economic elites, as well as, against supranational institutions and globalization, radical right parties have managed to gain many votes in countries that were severely hit by the global financial crisis in 2007 and 2008. Additionally, the migrant crisis in 2014 gave new impetus for the favorite radical right topic - immigration. By stressing out that migrants represent a cultural and economic threat to the domestic population in Europe, the radical right parties used the migrant crisis to spread their views and in return gain support. Defined as a serious and unique alternative to the traditional political parties, the rise of the radical right political parties very often was portrayed as the biggest danger to the European democracies. However, the Covid-19 outbreak has stopped their rise and in the short run, it has even decreased their ratings. The radical right political parties became completely lost during the Covid-19 outbreak due to the creation of the division of ,,them" vs. us", which in the light of Covid-19 was not effective. Additionally, speaking against globalization, supranational institutions, immigration and open borders during Covid-19 has lost its momentum. In that regard, it is becoming evident that radical right political parties are gaining momentum during the political, economic and migrant crises but they do not manage to use circumstances when it comes to the health crises. What remains to be answered is the question how radical right political parties will cope with the post-pandemic crises. Will they grow or will they continue to fall?
Keywords: politics, political system, political parties, radical right parties, crisis, Covid-19